The effects of sodium hydrogen carbonate ingestion during the recovery period between two 200-m front-crawl time trials - Ušaj, A.; Marcun, R.; Štrumbelj, B. (European Journal of Applied Physiology, 2024)
Purpose The aim of this study was to determine how sodium hydrogen carbonate (NaHCO3) ingestion during a 1-h recovery period after a 200-m front-crawl swim affects blood-gas levels, acid-base balance, and performance during a successive trial.